Tides in the Last Interglacial: insights from notch geometry and palaeo tidal models in Bonaire, Netherland Antilles. Issue 1 (December 2017) - Lorscheid, Thomas; Felis, Thomas; Stocchi, Paolo; Obert, J.; Scholz, Denis; Rovere, Alessio
Abstract The study of past sea levels relies largely on the interpretation of sea-level indicators. Palaeo tidal notches are considered as one of the most precise sea-level indicators as their formation is closely tied to the local tidal range. We present geometric measurements of modern and palaeo (Marine Isotope Stage (MIS) 5e) tidal notches on Bonaire (southern Caribbean Sea) and results from two tidal simulations, using the present-day bathymetry and a palaeo-bathymetry. We use these two tools to investigate changes in the tidal range since MIS 5e. Our models show that the tidal range changes most significantly in shallow areas, whereas both, notch geometry and models results, suggest that steeper continental shelves, such as the ones bordering the island of Bonaire, are less affected to changes in tidal range in conditions of MIS 5e sea levels. We use our data and results to discuss the importance of considering changes in tidal range while reconstructing MIS 5e sea level histories, and we remark that it is possible to use hydrodynamic modelling and notch geometry as first-order proxies to assess whether, in a particular area, tidal range might have been different in MIS 5e with respect to today.